1991
DOI: 10.5465/amr.1991.4278961
|View full text |Cite
|
Sign up to set email alerts
|

Equity, Equality, Power, and Conflict

Abstract: Although equity theory has dominated the conception oi justice in organizational reldions, equality also shapes justice expectations and behaviors. Therefore, there are two basic and, in principle, inevitable pressures toward conflict: (a) one stems from equity violations and results in overt conflict involving attempts to restore justice and (b) the other stems from equality violations and results in nondirected conflict that is symptomatic of decreased social cohesiveness. Power shapes distributive orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(127 citation statements)
references
References 58 publications
3
124
0
Order By: Relevance
“…Cooperation tends to become greater when resources are perceived to have been distributed equally rather than unequally. This is because equal distribution of resources enhances feelings of group harmony and social responsibility, and thus promotes cooperative response to resource scarcity (Deutsch, 1975;Kabanoff, 1991).…”
Section: Resource Scarcity: Cooperative Versus Conflict Responsesmentioning
confidence: 99%
“…Cooperation tends to become greater when resources are perceived to have been distributed equally rather than unequally. This is because equal distribution of resources enhances feelings of group harmony and social responsibility, and thus promotes cooperative response to resource scarcity (Deutsch, 1975;Kabanoff, 1991).…”
Section: Resource Scarcity: Cooperative Versus Conflict Responsesmentioning
confidence: 99%
“…Therefore, many landacquired households accepted handing over their land because they were aware of the potential costs if they had protested. These findings support Kabanoff (1991), Cosier and Dalton (1983), Weick (1966), Ring and Andrew (1994), and (Hayibor & Collins, 2016b) who suggested that the resource dependence and costs of reactions could mediate or prevent tough behavioural responses, and extend them further by recognising that the resource dependence and costs of reactions in land acquisition were created by the political environment.…”
Section: Political Environmentsupporting
confidence: 78%
“…This is because they could receive higher costs for their responses. Kabanoff (1991), Cosier and Dalton (1983), Weick (1966), Ring and Andrew (1994) also raised the importance of these moderators of responses. Social relationships are also moderators of responses to inequity.…”
Section: Moderators Of Responsesmentioning
confidence: 99%
“…By nature, organizations need to manage a fundamental paradox between inequality and solidarity-on one hand, organizational members must consent to differential distribution of status/power, resources, and opportunities to operate within hierarchy; on the other hand, leaders and followers need to work together to maintain group cohesiveness (Kabanoff, 1991). Power distance reflects organizational members' orientation toward the uneven allocation and inequality, whereas collectivism reflects the members' agreement to share common goals and relational identity.…”
Section: Hypothesis 1b: Transactional Leadership Is Negatively Associmentioning
confidence: 99%